QbD assisted RP-HPLC method for determination of Pyridoxine and Doxylamine in pharmaceutical formulation using central composite design - Gangu Naidu Challa, Daniel Raju Kunda, Sheik Jakir Hussain Mustaq, Nagabharathi Marni, Srilekhya Ketha, Urmila Gorle, Shravitha Jakkula, Bhagavan Rajesh Babu Koppisetty (Journal of Applied Pharmaceutical Science, 2025)
The quality by design enabled the development of cost-effective, simple, precise, and rapid RP-HPLC techniques for determining Pyridoxine (PRD) and Doxylamine (DXA) in the tablet dosage form. Systematic method optimization was performed through central composite design by altering the flow rate and composition of the organic phase in the mobile phase as the critical method parameters for evaluating the necessary analytical attributes, namely the tailing factor, theoretical plate count, and resolution. The optimal separation was achieved on a column with C18 in nature and dimensions of (250 mm length × 4.6 mm id × 5 μm particle size) composed of a blend of acetate buffer and acetonitrile in a volumetric composition of 35:65, at a flow rate of 1.0 ml/minute. Detection was carried out at 254 nm. The PRD and DXA have retention times of 3.053 and 4.357 minutes, respectively. The developed method was useful for the determination of bulk drugs and formulations.
Keywords: Pyridoxine, doxylamine, method validation, quality by design